2008
DOI: 10.1007/s10608-008-9200-3
|View full text |Cite
|
Sign up to set email alerts
|

Rumination in Interpersonal Relationships: Does Co-rumination Explain Gender Differences in Emotional Distress and Relationship Satisfaction Among College Students?

Abstract: Rose (Child Dev 73:1830-1843, 2002 found evidence that co-rumination accounts for girls' greater emotional distress as well as their greater friendship satisfaction compared to boys. Co-rumination is defined as a passive, repetitive discussion of symptoms or problems with a close other. The present study explored the associations between corumination in various types of close relationships and both emotional distress and relationship satisfaction in college students. First, confirmatory factor analyses demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
185
5
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(213 citation statements)
references
References 47 publications
20
185
5
3
Order By: Relevance
“…Consistent with past research (Calmes & Roberts, 2008;Rose, 2002;Rose et al, 2007), girls reported engaging in more co-rumination than boys. We also replicated past findings of gender differences in reports of depression and anxiety, with girls reporting significantly higher levels of internalizing symptoms (Rescorla et al, 2007).…”
Section: Gender Co-rumination and Peer/emotional Adjustmentsupporting
confidence: 87%
See 1 more Smart Citation
“…Consistent with past research (Calmes & Roberts, 2008;Rose, 2002;Rose et al, 2007), girls reported engaging in more co-rumination than boys. We also replicated past findings of gender differences in reports of depression and anxiety, with girls reporting significantly higher levels of internalizing symptoms (Rescorla et al, 2007).…”
Section: Gender Co-rumination and Peer/emotional Adjustmentsupporting
confidence: 87%
“…Our study contributes to a small body of research suggesting that co-rumination may be one gender-linked relationship process that helps explain gender differences in internalizing problems (Calmes & Roberts, 2008;Rose & Rudolph, 2006;Rose, 2002;Rose et al 2007). We extend this research in important new directions by examining associations with externalizing problems, aspects of peer relations previously neglected, and individual coping skills within a sample of middle adolescents.…”
Section: Discussionmentioning
confidence: 89%
“…In previous studies, co-rumination has been linked to depression (Calmes & Roberts, 2008;Rose, 2002;Rose et al, 2007;Schwartz-Mette & Rose, 2012;Starr & Davila, 2009;Stone, Hankin, Gibb, & Abela, 2011). Co-rumination may lead to depression because it involves a persistent negative focus and impedes activities that could offer distraction from problems (Rose et al, 2007).…”
Section: Trait Depression and Co-ruminationmentioning
confidence: 95%
“…Although rumination and co-rumination are very similar, scholars have examined rumination in comparison to co-rumination in order to substantiate that these two constructs are indeed different from one another (Calmes & Roberts, 2008;Stone et al, 2011;Jose et al, 2012). Jose, Wilkins, and Spendelow (2012) argued that co-rumination and rumination are distinguishable in that rumination is an individual's intrusive thoughts about one's problems, whereas co-rumination is an interpersonal process of discussing problems with others.…”
Section: Rumination and Co-ruminationmentioning
confidence: 99%
See 1 more Smart Citation